2013
DOI: 10.1073/pnas.1311314110
|View full text |Cite
|
Sign up to set email alerts
|

Sagebrush carrying out hydraulic lift enhances surface soil nitrogen cycling and nitrogen uptake into inflorescences

Abstract: Plant roots serve as conduits for water flow not only from soil to leaves but also from wetter to drier soil. This hydraulic redistribution through root systems occurs in soils worldwide and can enhance stomatal opening, transpiration, and plant carbon gain. For decades, upward hydraulic lift (HL) of deep water through roots into dry, litter-rich, surface soil also has been hypothesized to enhance nutrient availability to plants by stimulating microbially controlled nutrient cycling. This link has not been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 35 publications
2
60
0
Order By: Relevance
“…S7 and S8). This sensitivity to plant-driven flow supports the body of literature arguing that plant control of water use, both rates of daytime transpiration and nighttime water use (i.e., nighttime transpiration and nighttime root-water release), can modify nutrient availability within the rhizosphere and alter plant nutrient uptake (e.g., Snyder et al 2008;Cramer et al 2009;Cardon et al 2013;Cernusak et al 2011;Matimati et al 2014;Graciano et al 2016). The second implication of Fig.…”
Section: +supporting
confidence: 75%
See 1 more Smart Citation
“…S7 and S8). This sensitivity to plant-driven flow supports the body of literature arguing that plant control of water use, both rates of daytime transpiration and nighttime water use (i.e., nighttime transpiration and nighttime root-water release), can modify nutrient availability within the rhizosphere and alter plant nutrient uptake (e.g., Snyder et al 2008;Cramer et al 2009;Cardon et al 2013;Cernusak et al 2011;Matimati et al 2014;Graciano et al 2016). The second implication of Fig.…”
Section: +supporting
confidence: 75%
“…A constant water potential of −0.5 MPa was prescribed at the bulk-soil boundary (Ψ sb ) and a time-varying water potential was prescribed at the root-soil interface (Ψ sr ), mimicking daily oscillations in soil water potential measured in natural ecosystems (e.g., Meinzer et al 2004;Cardon et al 2013) and establishing unsaturated, diel water-flow across the soil domain. This approach assumes no competition for water between neighboring roots and captures flow conditions with the bulk soil water potential poised at an ecologically relevant point.…”
Section: Boundary Conditions -Unsaturated Flowmentioning
confidence: 99%
“…Previous studies have indicated that plant species significantly affect soil water and nutrient availability due to having different hydraulic lift capacities (Cardon, Stark, Herron, & Rasmussen, ), input quantities and qualities of litter and root exudates (Haichara, Santaella, Heulin, & Achouak, ; Tsunoda & van Dama, ), and directions and strengths of the rhizosphere priming effect (Finzi et al, ; Huo, Luo, & Cheng, ). Similarly, this research also showed that many soil physicochemical properties differed significantly among the three plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HR may play important roles for increasing nutrient availability in surface soil layers (Cardon et al . ). For many grassland systems, nutrient availability is highest in the surface soil layers (Ajwa, Rice & Sotomayor ), with mineralization rates correlated with changes in soil moisture (Stanford & Epstein ).…”
Section: Next Stepsmentioning
confidence: 97%